A comunidade de blogs myopera como ambiente virtual de aprendizagem para ensinar química no ensino médio: um estudo de caso - Silva, Clauton Moreira da (2012)
The aim of the present work is to evaluate the processes of production and application of virtual learning environments from the blogging community MyOpera in Chemistry teaching to high school students, as well as discussing their results. The problem of this survey highlights the figure of the teacher, his interaction with cyberculture and his teaching methodology, and presents itself as follows: how Chemistry teachers can use the blogging community MyOpera as virtual learning environment to teach Chemistry in high school? The teaching of Chemistry in these virtual environments is the focus of this research. In this context, it was analyzed the behavior of school in these post-modern times, from the perspective of Giroux, and how teachers of Sciences, particularly Chemistry, have not yet managed to extricate themselves from teaching based on traditional inductive-positivist common sense as Maldaner, Carvalho and Gil-Perez suggest. It was also studied the Digital Culture which appeared with the computer and became the “media of the medias” in the texts of Santaella and Lèvy. We also discussed how the new information and communication technologies (NICTs) can be used in the classroom within the constructionist reading patterns covered in Valente. Basing on Prado and Valente, it was discussed how the teacher's participation happens in constructionism. In field research, the study took into consideration the concept of design interaction by Preece et al., defined as a blogosphere in the light of Recuero, Barbosa and Granado and Lara, and the concept of virtual learning environment in the reading of Santos and Okada, justifying the building of virtual learning environment in the blogging community MyOpera. The field research raised data through questionnaires and interviews applied to two teachers responsible for the teaching of Chemistry in a military school located in Fortaleza, and to a group of 24 students from a class of second year of high school in this same institution. The interviews were analyzed by the technique of content analysis proposed by Bardin and, at the end, it made us approach the goal of analyzing what was the influence of a virtual learning environment produced in a blogosphere, among the teachers in the teaching of Chemistry.